2012
DOI: 10.1128/jvi.00599-12
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Based Vaccination with a Mismatched Envelope Protects against Simian Immunodeficiency Virus Infection in Nonhuman Primates

Abstract: The RV144 trial demonstrated that an experimental AIDS vaccine can prevent human immunodeficiency virus type 1 (HIV-1) infection in humans. Because of its limited efficacy, further understanding of the mechanisms of preventive AIDS vaccines remains a priority, and nonhuman primate (NHP) models of lentiviral infection provide an opportunity to define immunogens, vectors, and correlates of immunity. In this study, we show that prime-boost vaccination with a mismatched SIV envelope (Env) gene, derived from simian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Thus, much more needs to be understood about structure-function-antigen relationships of HIV-1, HIV-2, and the SIV strains that are used to model these important human pathogens. In the meantime, the exquisite neutralization sensitivity and heterogeneity in the SIVsmE660 isolate are relevant to the interpretation of recent NHP vaccine challenge studies demonstrating significant, but incomplete, vaccine-induced protection from repeated lowdose mucosal challenge with SIVsmE660 (24,101,102). Indeed, our data suggest the possibility that the variable protection afforded by heterologous immunization in animals challenged mucosally with SIVsmE660 may be due to vaccine-induced protection only against the majority population of highly sensitive viruses, with breakthrough infections arising from the minority population of resistant viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, much more needs to be understood about structure-function-antigen relationships of HIV-1, HIV-2, and the SIV strains that are used to model these important human pathogens. In the meantime, the exquisite neutralization sensitivity and heterogeneity in the SIVsmE660 isolate are relevant to the interpretation of recent NHP vaccine challenge studies demonstrating significant, but incomplete, vaccine-induced protection from repeated lowdose mucosal challenge with SIVsmE660 (24,101,102). Indeed, our data suggest the possibility that the variable protection afforded by heterologous immunization in animals challenged mucosally with SIVsmE660 may be due to vaccine-induced protection only against the majority population of highly sensitive viruses, with breakthrough infections arising from the minority population of resistant viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The RV144 clinical trial showed modest protection against infection, and this protection apparently correlated with anti-Env bAb, especially IgG antibodies against the V1V2 region (22, 23), but no evidence of vaccine-induced virus control was found in the individuals who became infected. Clearly, a vaccine regimen able to prevent acquisition (11,19,20,24) and reduce viral replication after infection has become possible (11,19,24) using the macaque model. In agreement with those findings, we report that our SIVmac239-based vaccine elicited systemic and mucosal anti-Env humoral immune responses able to significantly delay acquisition of the heterologous SIVsmE660, and SIV-specific cellular responses that efficiently contribute to postacquisition control of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, passive administration of neutralizing monoclonal antibodies (nmAbs) to nonhuman primates (NHPs) has repeatedly been shown to provide robust protection against mucosal infection with a chimeric human/simian immunodeficiency virus, even at modest in vitro nAb IC 50 titers that are readily achievable by vaccination (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). NHP studies have also demonstrated that protection against heterologous SIV challenge is feasible and likely mediated by antibody responses (15)(16)(17)(18). We recently reported on the protective efficacy and immune responses elicited by SIVmac239-based DNA-prime/modified vaccinia virus Ankara-boost (DDMM) vaccination of rhesus macaques (RMs), with GM-CSF adjuvant (DgDgMM), CD40-ligand adjuvant (D 40L D 40L MM), or administering three MVA immunizations without DNA priming (MMM) (Fig.…”
mentioning
confidence: 99%